Towards interactive haptic simulation of cutting. (8th March 2010) - Payandeh, Shahram; Zhang, Hilary; Cha, Jekeon
In this paper, we use an enhanced surface mass-spring model to simulate virtual dissection by progressive subdivision and re-meshing for cutting and cross-cutting. We introduce novel algorithms to generate interior structures that show the result of cutting generated by the interaction between instrument and model. Our simulator supports two types of cutting: 'cut-into', in which the instrument only penetrates the simulated tissue, and 'cut-through' in which the instrument cuts completely through. Haptic force feedback models for interaction between virtual instruments and object are also implemented, which allows the user to feel the contact forces through a haptic device.